Remontage of the history - Simonson, Patricia (My University, 2024)
In terms of the architectural production today, the question of architectural continuity is highly relevant, particularly in a growing city like Gothenburg where the issue has become widely debated in recent years. It is believed that architects reasonably have more knowledge than politicians about the challenges of their industry. Thus, the task of designing the city should be assigned to them. At the same time the appearance and living environment of a city affects everyone who lives in it. Architecture could be considered as an art form, but also as a social benefit where the opinions of politicians and citizens must be considered. There are different approaches when designing a new building. Some mean that the architectural production should mimic the historical building context in order to create a cohesive city. On the other hand, it is also believed that new buildings must relate to the present. This thesis aims to reflect upon the concept of designing with historical consciousness and what it could mean for the expression of a building. The purpose is to explore how a contemporary addition can be designed at Fjärde Långgatan in Gothenburg with the main focus of the relationship between contemporary and history. The investigation is made through research by design, where an indepth analysis of the existing built environment forms the basis of the design proposal. The process is conducted and explored through sketches, drawings, digital modelling and with a great focus on physical models. The proposal strives to create a sustainable architecture, both in terms of architectural robustness as well as in the choice of materials, where historic building references in nature of rhythm, proportions and details have been an important source of inspiration
Keywords: Architectural continuity, historical consciousness, contemporary addition